Performance and Meat Quality of Broilers Infected with Escherichia coli and Administered with Bio Additive, Probiotic, and Antibiotic - L Istiqomah; S N Hayati; E Damayanti; H Julendra; A A Sakti; T Untari (Faculty of Animal Science, Bogor Agricultural University, 2013)
An experiment was conducted to determine the efficacy of bio additive administration (a mixture of Lumbricus rubellus extract, Morinda citrifolia leaves extract and lactic acid bacteria), probiotic, and antibiotic to the performance and meat quality of broiler infected with Avian Pathogenic Escherichia coli (APEC). In this study, 140 Jumbo 747 unsexed one-day old chicks were distributed randomly into 20 units of cages, each filled with 7 broilers. Twenty cages were assigned into 5 treatment groups, each treatment in 4 equal replicates. The treatments were as follows: A= E. coli infection (positive control), B= E. coli infection + bio additive, C= E. coli infection + probiotic, D= E. coli infection + antibiotic, E= No E. coli infection (negative control). A commercial corn-soybean-based broiler diet was formulated as the basal diets. The experimental period was 35 d and at 21st d of age the broilers were infected with E. coli except the E treatment. The result showed that bio additive administration (B) increased the final body weight (1,659.52 g) and body weight gain (1,616.81 g) and resulted in less FCR (1.87) among other treatments. The lowest mortality rate was recorded in B treatment (3.57%) and D treatment (3.57%). Probiotic (C treatment) and antibiotic (D treatment) decreased (P < 0.05) meat pH and tenderness compared to other treatments. Meanwhile bio additive administration did not affect the meat quality (pH, cooking loss, water-holding capacity, tenderness, and fat) compared to positive and negative controls. The lowest meat cholesterol content was observed in B treatment (54.02 mg/100 g). It is concluded that bio additive administration on broiler infected with E. coli increased the broiler performance and decreased the meat cholesterol compared to other treatments.